2021
DOI: 10.3389/fcimb.2021.728415
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Intrahost Dynamics of the Second Human Pegivirus and Hepatitis C Virus in HPgV-2/HCV-Coinfected Patients

Abstract: BackgroundThe second human pegivirus (HPgV-2) and hepatitis C virus (HCV) belong to the Flaviviridae family and share some common genome features. However, the two viruses exhibit significantly different genetic diversity. The comparison of intrahost dynamics of HPgV-2 and HCV that mainly reflect virus-host interactions is needed to elucidate their intrahost difference of genetic diversity and the possible mechanisms.MethodsIntrahost single nucleotide variations (iSNVs) were identified by means of next-generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Our previous studies showed that sofosbuvir can inhibit HCV replication but not HPgV-2 replication ( 13 , 14 ). Sofosbuvir is a uridine analog and a nucleotide inhibitor (NI) of RdRp for the treatment of chronic HCV infection ( 21 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies showed that sofosbuvir can inhibit HCV replication but not HPgV-2 replication ( 13 , 14 ). Sofosbuvir is a uridine analog and a nucleotide inhibitor (NI) of RdRp for the treatment of chronic HCV infection ( 21 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Forberg et al suggested that the relationship between HPgV-2 and HCV is commensal but not dependent ( 12 ). It is hypothesized that, with reliance on HCV, HPgV-2 would be under minimal selective pressure and maintain its sequence fidelity within the host ( 13 ). We emphasize that as the fidelity of HPgV-2 RdRp was evaluated only in in vitro polymerase assays, our results may not completely reflect the true behavior of HPgV-2 RdRp in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations